2015
DOI: 10.1007/s11103-015-0370-6
|View full text |Cite
|
Sign up to set email alerts
|

Target of rapamycin (TOR) plays a critical role in triacylglycerol accumulation in microalgae

Abstract: Most microalgae produce triacylglycerol (TAG) under stress conditions such as nitrogen depletion, but the underlying molecular mechanism remains unclear. In this study, we focused on the role of target of rapamycin (TOR) in TAG accumulation. TOR is a serine/threonine protein kinase that is highly conserved and plays pivotal roles in nitrogen and other signaling pathways in eukaryotes. We previously constructed a rapamycin-susceptible Cyanidioschyzon merolae, a unicellular red alga, by expressing yeast FKBP12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 34 publications
5
105
0
1
Order By: Relevance
“…7 Based on these findings, it was concluded that the TOR-signaling pathway negatively regulates TAG accumulation in microalgae. 8 Mammalian TOR (mTOR) inhibitors are generally used as immunosuppressors as well as antineoplastic drugs in various cancer treatments. 9 Therefore, development of new chemicals that specifically inhibit mTOR activity has been an intensive research area for future medical applications.…”
Section: Tor (Target Of Rapamycin) Is a Key Regulator Of Triacylglycementioning
confidence: 99%
“…7 Based on these findings, it was concluded that the TOR-signaling pathway negatively regulates TAG accumulation in microalgae. 8 Mammalian TOR (mTOR) inhibitors are generally used as immunosuppressors as well as antineoplastic drugs in various cancer treatments. 9 Therefore, development of new chemicals that specifically inhibit mTOR activity has been an intensive research area for future medical applications.…”
Section: Tor (Target Of Rapamycin) Is a Key Regulator Of Triacylglycementioning
confidence: 99%
“…This is consistent with the reports on other microalgae including Cy. merolae, which accumulate nonpolar lipids under nutrient deprivation (Chisti, 2007;Hu et al, 2008;Imamura et al, 2015;Iwai et al, 2014;Moellering & Benning, 2010;Msanne et al, 2012;Sakurai et al, 2014;Siaut et al, 2011;Tornabene et al, 1983). Compared with other microalgae, Cy.…”
Section: Discussionmentioning
confidence: 99%
“…We still need to know which of the three DGATs in Cy. merolae (CME100C, CMJ162C and CMQ199C) (Imamura et al, 2015;Sumiya et al, 2015) determines the specificity of acylation.…”
Section: Structure Of Tag and Role Of Pc In Tag Synthesismentioning
confidence: 99%
See 2 more Smart Citations